2007
DOI: 10.3748/wjg.v13.i38.5079
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects and mechanisms of Baicalin and octreotide on renal injury of rats with severe acute pancreatitis

Abstract: AIM:To i n v e s t i g a t e t h e p r o t e c t i v e e f fe c t s a n d mechanisms of Baicalin and octreotide on renal injury of rats with severe acute pancreatitis (SAP). METHODS:One hundred and eighty SD rats were randomly assigned to the model group, Baicalin-treated group, octreotide-treated group and sham operation group. The mortality, plasma endotoxin level, contents of blood urea nitrogen (BUN), creatinine (CREA), phospholipase A2 (PLA2), nitrogen monoxide (NO), tumor necrosis factor (TNF)-α, IL-6 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 23 publications
1
71
0
Order By: Relevance
“…In one experimental animal study, Zhang XP et al reported some protective effects and the mechanism of Baicalin and Octreotide on renal injury in rats with SAP. The authors showed from histopathological tissue microarray sample of kidney inhibition of inflammatory mediators, decreasing the expression level of Bcl-2 protein and enhancing the apoptosis-promoting effect of Bax dimmer to induce apoptosis of renal tubular cells 104 .…”
Section: Renal Function Supportive Measuresmentioning
confidence: 99%
“…In one experimental animal study, Zhang XP et al reported some protective effects and the mechanism of Baicalin and Octreotide on renal injury in rats with SAP. The authors showed from histopathological tissue microarray sample of kidney inhibition of inflammatory mediators, decreasing the expression level of Bcl-2 protein and enhancing the apoptosis-promoting effect of Bax dimmer to induce apoptosis of renal tubular cells 104 .…”
Section: Renal Function Supportive Measuresmentioning
confidence: 99%
“…After systemic inflammatory response syndrome (SIRS) was introduced, the important role of excessive inflammatory reaction in the pathogenesis of SAP has been gradually recognized [31][32][33][34]. The symptoms, such as disorientation, clouding of consciousness, as well as agitation accompanied by delusions and hallucinations, present in acute pancreatitis is called pancreatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, baicalin also has some protective effects on the nervous system [16][17][18][19]. These observations suggest that baicalin may be used to treat SAP [20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…The standards for the pathological severity scores of pancreas, liver, kidney, and lung have been shown in our series of reports [8,21,22]. The standard for the pathological severity score for the spleen was as follows: a score of 0 was assigned if spleen structure was normal; 1 if necrosis in follicular center was seen; 2 if blood sinus expansion and arteriolosclerosis were observed; 3 if necrosis in follicular center, blood sinus expansion, and arteriolosclerosis were observed.…”
Section: Observation Indexesmentioning
confidence: 99%